On equivalence of parameterized surfaces with respect to linear change of parameters - Bekbaev, Ural (University Putra Malaysia (UPM) Press, 2016)
The equivalence problem of parameterized surfaces with respect to linear changes of parameters is considered. Separating systems of invariants and uniqueness theorem are offered. The field of invariant differential rational functions over the constant field is described as a differentialfield by giving a finite system of generators.